Rancang Bangun Mesin Sekur Klep Dengan Sistem Pneumatik - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Rizal Noor Aditiya, Suyadi, dan Agus Pramono (Teknis, 2015)
The purpose of this research is to design and create a machine that can be used in the process mensekur valve on the engine block motorcycle using pneumatic system as a clamp block engine and a driving rack and pinion steering as a function of substitute motions human hand so it can be set up and operated automatic in order to penyekuran saves time, because the process of manually penyekuran usual can take a long time about 90 minutes. How to operate the machine sekur valve by using the development of electoral observation in the form of alternative designs, design, manufacturing, assembly up until the testing process and data retrieval. Results of machinery sekur valve with pneumatic system can repair a valve leak on a motorcycle with penyekuran process an average of 7 minutes.Keywords: Sekur valve, engine block, motorcycle, and pneumatic.